MASUKNYA PENGUNGSI YAMAN KE KOREA SELATAN PADA TAHUN 2018 - Arni Anggraeni; Ahmad Jamaan (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2023)
ABSTRACT Yemen is having a humanitarian crisis due to the conflict caused by Houthi. This humanitarian crisis has caused many Yemeni people to flee to other countries to seek protection. In 2017, South Korea opened direct flights from Kuala Lumpur to Jeju Island. Yemeni refugees who stayed in Malaysia decided to seek protection to Jeju Island because Malaysia has not ratified the 1951 Convention on Status of Refugees. Due to the reason, Yemeni refugees could not stay for long in Malaysia and had to flee to other countries. Meanwhile, South Korea has ratified 1951 Convention on Status of Refugees and can provide protection to refugees. There are 561 Yemeni refugees who entered Jeju Island to seek protection. This research found that the conditions of Yemeni people really need help from other countries that have ratified refugee agreement to help them. However, South Korea was not ready to handle Yemeni Refugees who came in 2018 which caused problems to refugees. Keywords : Jeju Island, Yemeni Refugees, 1951 Convention on Status of Refugees